Protective effects of broccoli extracts and sulforaphane against hydrogen peroxide induced oxidative stress in B16 cells - Yao Zhang (Elsevier, 2021)
The antioxidant activity of broccoli extracts and its purified compounds (polyphenols and purified sulforaphane (PSF)) was investigated. Broccoli extracts and SF protected B16 cells from H2O2-induced oxidative stress through increasing total antioxidant capacity (T-AOC) and activities of NADPH dehydrogenase quinone1 (NQO1) and catalase (CAT), and decreasing content of malondialdehyde (MDA). Western blot and qRT-PCR revealed that the expression of nuclear factor erythroid 2-related factor 2 (Nrf2), NQO1 and heme oxygenase 1 (HMOX-1) was increased. Broccoli extracts was better than SF in improving T-AOC, antioxidant enzyme activity (especially, NQO1) and reducing MDA content. Polyphenols and PSF were separated from broccoli extracts by high-speed countercurrent chromatography (HSCCC). They could significantly increase T-AOC and NQO1 activities (P < 0.05). PSF increased activities of Phase 2 enzymes more than polyphenols. Broccoli extracts protected B16 cells from H2O2-induced oxidative stress via enhancing Nrf2/Keap1 signaling pathway. The protection was mainly attributable to SF, followed by polyphenols.